2007
DOI: 10.1002/cncr.22358
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of African American cancer survivors

Abstract: KEYWORDS: African American, quality of life, cancer survivors, breast cancer, prostate cancer, literature review, integrative research reviews. D espite advances in cancer care and increases in rates of survival over the past decades, cancer is second only to heart disease as the leading cause of death in the United States. 1 African Americans have higher incidence and/or mortality rates and lower rates of survival for many cancers when compared with other racial/ethnic groups. For example, African American me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…Whether there are racial or ethnic differences in mental-health–related quality of life among cancer survivors remains unclear. Several studies have found no racial/ethnic differences [12, 13]; other studies have found that African Americans (commonly breast cancer survivors) report better emotional well-being than whites [16]; and a few studies have reported lower mental-health–related quality of life among Hispanics, Asian Americans, or African Americans [13, 14]. Poor mental health is associated with risk factors and poor outcomes in the general population, where associations have been found between depression and nonadherence to medical treatment [17] and between depression and increased use of medical services [18]; similar associations have been found among cancer survivors, in whom depression has been found to be associated with maladaptive health behaviors and poorer overall survival [19].…”
Section: Factors Affecting Quality Of Life In Cancer Survivorsmentioning
confidence: 99%
“…Whether there are racial or ethnic differences in mental-health–related quality of life among cancer survivors remains unclear. Several studies have found no racial/ethnic differences [12, 13]; other studies have found that African Americans (commonly breast cancer survivors) report better emotional well-being than whites [16]; and a few studies have reported lower mental-health–related quality of life among Hispanics, Asian Americans, or African Americans [13, 14]. Poor mental health is associated with risk factors and poor outcomes in the general population, where associations have been found between depression and nonadherence to medical treatment [17] and between depression and increased use of medical services [18]; similar associations have been found among cancer survivors, in whom depression has been found to be associated with maladaptive health behaviors and poorer overall survival [19].…”
Section: Factors Affecting Quality Of Life In Cancer Survivorsmentioning
confidence: 99%
“…Physical symptoms can be the most burdensome and are among the most persistent sequelae of cancer and its treatments. Several studies report that ethnic minority BCS showed notably poorer outcomes in PQOL specifically, compared to European American survivors [14,[63][64][65][66]. This small but growing body of research suggests that ethnic variability in overall HRQOL and PQOL exists.…”
Section: The Contextual Model Of Hrqolmentioning
confidence: 99%
“…The most often cited limitation is the non-representativeness of the study sample, therefore limiting the generalizability of the findings [27]. It also remains poorly understood if these interventions are able to adequately address the socio-cultural factors germane to African Americans that impact health outcomes [27].…”
Section: Introductionmentioning
confidence: 99%
“…The most often cited limitation is the non-representativeness of the study sample, therefore limiting the generalizability of the findings [27]. It also remains poorly understood if these interventions are able to adequately address the socio-cultural factors germane to African Americans that impact health outcomes [27]. Given the disproportionate impact of this disease on African Americans, it is important to improve upon and expand the current body of science to ensure interventions are developed to specifically address the most salient and unique issues of these survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation